Key elements of sports techniques of ball throwing and catching by those engaged in rhythmic gymnastics at the stage of preliminary basic preparation - Andreyeva, N. O. (Journal of Physical Education and Sport, 2013)
New scientific facts of the efficient biomechanical analysis and evaluation of indices of ball throwing and catching sports techniques kinematic structure are presented in the paper. The method of postural motion reference points in phase structure of basic connecting moves of exercises ball throwing and catching (performed by gymnast O.P., the international class master as well as young gymnasts (n=20) of the stage of preliminary basic preparation) has allowed to single out the key elements of sports techniques: in the phase of preparatory motor actions - body launching posture, in the phase of major motor actions - multiplication of body postures, and in the phase of concluding motor actions - concluding body posture (landing to stop or transition). The above has permitted to objectively analyze sports techniques of exercises, reveal the causes of technical faults during formation of motor skill of ball throwing and catching, and determine perspectives of development of didactic algorithm of training and sports preparation. Methods. Theoretical analysis and generalization of data of scientific and methodical literature and practical experience, usage of questionnaires for questioning coaches in rhythmic gymnastics, pedagogical observation, method of postural motion reference points (V. N. Boloban, 1990), biomechanical video computer analysis of kinematic structure of ball throwing and catching sports techniques (BioVideo method I. V. Khmelnitskaya, 2000), method of expert estimations, pedagogical experiment, mathematical statistics. Results: In phase structure of basic connecting moves of rhythmic gymnastics exercises: from 2 3 steps ball throwing during kazachok jump execution - ball catching to roll over both arms and back while making rhythmical steps and: from 2 3 steps - ball throwing during jump followed by rear leg touching the head, thus forming the ring - ball catching to roll over both arms and back while making rhythmical steps, performed by top level female gymnast and her young colleagues, the key elements of sports techniques have been recorded. In phase of preparatory motor action - body launching posture; in that of major motor actions - multiplication of body posture; and in that of concluding motor actions - concluding body posture. Kinematic structure indices of basic connecting moves of ball exercises performed by gymnast O.P., international class master in rhythmic gymnastics have been estimated by experts as the results, which could serve as the sports technical landmarks for coaches and young female gymnasts of the preliminary basic preparation stage providing the development of new methods of training of ball throwing and catching. Discussion and conclusions: Results of studies are in agreement with data obtained by specialists in the field of training exercises of sports events of gymnastics. In particular, the authors [3,4,5,14,15] have demonstrated that preceding element of motion (or posture) performed correctly from technical point of view carries in itself the features (speed strength, dexterous, spatial and temporal, amplitude, tempo rhythmical, psychomotor) to the subsequent motion (posture). Therefore, exercises are performed without unnecessary motor reorganizations and technical faults are not accumulated in exercises. On that ground the method of postural motion reference points has been used for biomechanical analysis and evaluation of ball throwing and catching, which allows to isolate and study the key elements of sports techniques in phase structure of exercise